Impact of cognitive performance and negative symptoms on psychosocial functioning in Czech schizophrenia patients - Kalisova, L; Michalec, J; Dechterenko, F; Silhan, P; Hyza, M; Chlebovcova, M; Brenova, M; Bezdicek, O (Schizophrenia (Heidelberg, Germany), 2023)
Schizophrenia has a profound influence on the real-life functioning of patients. There are several factors inherent to the disease course affecting the level of psychosocial functioning. Our study focused on the impact of cognitive deficit and severity of negative symptoms (i.e., the experiential domain (avolition, asociality, and anhedonia) and the expressive domain (blunted affect and alogia)) to explore psychosocial functioning in schizophrenia. Schizophrenia patients (n = 211) were tested for the presence of cognitive impairment using the NIMH-MATRICS: Measurement and Treatment Research to Improve Cognition in Schizophrenia Consensus Cognitive Cattery (MCCB; MATRICS Consensus Cognitive Battery) and the extent of negative symptoms using the PANSS (PANSS; Positive and Negative Syndrome Scale-selected items). The level of psychosocial functioning was measured with the Personal and Social Performance Scale (PSP). The path analysis using three regression models was used to analyse variables influencing psychosocial functioning (PSP). One of these models analyzed influence of cognitive functioning (MCCB) and negative schizophrenia symptoms (PANSS selected items reflecting expressive and experiential deficits) as predictors and NART/CRT and disease length as confounders. R2 was 0.54. The direct effect of the MCCB (β = 0.09) on the PSP was suppressed by the strong effect of the negative symptoms (β = -0.64). The presence of cognitive deficits and negative symptoms in our sample of schizophrenia patients significantly influences the level of their psychosocial functioning, a key factor in remission and recovery.